Evaluation of Salt Tolerance in Four Species of Annual Sesbania - Patcharaporn Phupaibul; Toru Matoh; Eiichi Takahashi (Agriculture and Natural Resources, 1993)
Hydroponic culture experiment was performed to evaluate salt tolerance potential of four species of annual Sesbania; S. rostrata, S. cannabina, S. speciosa and S. aculeata. Plant growth responded to salinity differently from species to species. About 24 to 58% reduction in growth was found at moderate salinity (30 mM). Among four species, S. rostrata showed the most favourable growth even under high salinity, followed by S. cannabina. The lower Na accumulation in the leaves than in other parts was apparently an adaptive feature in these legumes under salt stress condition. The changes in other mineral content differed from parts to parts. K and N content were adversely affected by the increasing salinity. A drastic decrease in Ca, Mg and P content could not be found. Leaf sap determination indicated that osmotic pressure in all species increased with the rising external osmotic pressure. The osmotic adjustment were mainly achieved by Na salt accumulation. The different response was found in S. aculeata which accumulated lower Na and higher K in its leaf sap. A notable role of organic constituents in osmotic adjustment was not observed.